2021
DOI: 10.3389/fcell.2021.778826
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Action of Canmei Formula Against Colorectal Adenoma Through Multi-Omics Technique

Abstract: Background: Canmei formula (CMF) is a traditional Chinese medicine compound with definite effect on the prevention and treatment of colorectal adenoma (CRA). CMF can prevent the transformation of intestinal inflammation to cancer. This study explored the mechanism of action of CMF in anti-CRA using multi-omics techniques.Method: The mice were randomly divided into four groups: blank group (Control), high-fat diet (HFD) + AOM/DSS colorectal adenoma model (ADH) groups, Canmei formula treatment group (ADH-CMF) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Research has shown that the AKT/mTOR, NF-κB, and ERK/MAPK signaling pathways are closely related to tumor EMT 13 , 14 . Besides, LHPP has been proven to have a strong connection with PI3K/AKT 7 , 9 , 15 , 16 . Thus, we examined whether LHPP affects biological behavior through PI3K/AKT/mTOR axis in GC.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that the AKT/mTOR, NF-κB, and ERK/MAPK signaling pathways are closely related to tumor EMT 13 , 14 . Besides, LHPP has been proven to have a strong connection with PI3K/AKT 7 , 9 , 15 , 16 . Thus, we examined whether LHPP affects biological behavior through PI3K/AKT/mTOR axis in GC.…”
Section: Resultsmentioning
confidence: 99%
“…While there was a decrease in the genetic expression of Ifn-γ in this study, it was not significant. Nowadays, microbiome and transcriptome have been widely used in biological research to provide a comprehensive understanding of gene expression [32]. As such, 16S rRNA sequence analysis indicated that PC significantly changed the composition of mice gut microbiota by decreasing Firmicutes, Deferribacteres, Proteobacteria, Cyanobacteria and Epsilonbacteraeota at the phylum level.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore identified the differentially expressed genes (DEGs) between AD mice and PC100 group mice following the cutoff criteria fold-change |log2FC| ≥ 1 and p-value < 0.05. A library with size-normalized count for the specimen was generated by making volcano plots for the DEGs as described elsewhere (Figure 5A,B) [32]. pathway was the IL-17 signaling pathway.…”
Section: Transcriptome Analysis Of Genes Expressed In Cac Micementioning
confidence: 99%
“…Further research may reveal more targets and pathways involved in inflammatory responses. As currently reported, 51 one or more pathways may participate in the anti‐inflammatory effect of TCM. In fact, due to the complexity of Chinese medicine and the inter‐relationship of signaling pathways, TCM, especially Chinese medicine preparations, may affect most of the signaling pathways.…”
Section: The Classic Mechanisms Of the Anti‐inflammatory Effects Of T...mentioning
confidence: 66%